Nonpharmacological Compensation of Aggressive Behavior of Individuals with Moderate Intellectual Disability and Behavioral Disorders-A Case Study - Vostrý, Michal; Lanková, Barbora; Pešatová, Ilona; Fleischmann, Otakar; Jelínková, Jaroslava (International journal of environmental research and public health, 2022)
The article discusses issues associated with the manifestations of aggressive behavior in an individual diagnosed with moderate intellectual disability and behavioral disorders (according to ICD-10; F7; F711-moderate intellectual disability, significant impairment of behavior requiring attention or treatment). In the research survey, we focused on a client corresponding with relevant features. The research was carried out at the beginning of hospitalization, ongoing hospitalization, and the end of hospitalization, followed by a recommendation to limit the legal capacity of the client and his placement in a residential care home. The case study points out individual approaches to special education and psychology and outlines the key steps in the cooperation of selected helping professions suggesting conclusions and recommendations for practice regarding these selected issues. Upon the termination of our investigation, there was a rapid deterioration of the client being admitted to the intensive care unit with a follow-up treatment in a long-term intensive care unit.
Keywords: jednotky intenzivní péče; agrese; Intensive Care Units; lidé; Humans; hospitalizace; Intellectual Disability; Hospitalization; Aggression; mentální retardace